(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
Nietzsche called love and hate ’magnificent monsters’. Proust referred to them as ’upheavals of thought’. Crucial in undermining our craving for mastery over uncertainty, they spur us to overcome mere rationality in favour of ’hyper-reflection’ (Merleau-Ponty). What is existential psychotherapy’s role in a cultural landscape subject to the wish to reprogramme our emotions?